2022
DOI: 10.1038/s41598-022-09027-w
|View full text |Cite
|
Sign up to set email alerts
|

BMI, sex and outcomes in hospitalised patients in western Sweden during the COVID-19 pandemic

Abstract: High body mass index (BMI) is associated with severe COVID-19 but findings regarding the need of intensive care (IC) and mortality are mixed. Using electronic health records, we identified all patients in western Sweden hospitalised with COVID-19 to evaluate 30-day mortality or assignment to IC. Adjusted logistic regression models were used to estimate odds ratios (OR) and 95% confidence intervals (CI) for outcomes. Of totally 9761 patients, BMI was available in 7325 (75%), included in the study. There was a m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 35 publications
2
5
0
Order By: Relevance
“…Furthermore, subgroup analysis based on matched cohort studies to minimize selection bias also supported the beneficial effects of previous BS on the reduction of the risks of ICU admission, mechanical ventilation, and mortality. Our results were consistent with the previous finding that obesity is a recognized risk factor for the need of intensive care [6] , [7] , [25] , highlighting the potential benefits of weight reduction in the critical care setting.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Furthermore, subgroup analysis based on matched cohort studies to minimize selection bias also supported the beneficial effects of previous BS on the reduction of the risks of ICU admission, mechanical ventilation, and mortality. Our results were consistent with the previous finding that obesity is a recognized risk factor for the need of intensive care [6] , [7] , [25] , highlighting the potential benefits of weight reduction in the critical care setting.…”
Section: Discussionsupporting
confidence: 93%
“…For the current study, we defined obesity as individuals with a body mass index (BMI) ≥30 mg/kg 2 in both the BS and control groups [24] . Besides, a previous study has reported an association between BMI≥30 kg/m 2 and the need for intensive care in patients diagnosed with COVID-19 [25] ; and (c) Availability of at least one prognostic outcome including the rates of COVID-19 infection, hospital admission, ICU admission, mechanical ventilation, overall mortality, and AKI. The exclusion criteria were (1) studies focused on pediatric or pregnancy population, and (2) those published as letters, case reports, conference abstracts, reviews, or other forms instead of original articles.…”
Section: Methodsmentioning
confidence: 98%
“…The present study confirmed findings from earlier studies that suggested male and older adults may be independent risk factors of hospital and/or ICU admission [ 37 , 42 , 43 , 44 ]. Consistent with a recent meta-analysis of 11,550 individual records [ 44 ], the present study revealed that individuals aged 70 and above and male remain significantly associated with hospitalization.…”
Section: Discussionsupporting
confidence: 92%
“…8,9 Patients of ages 25 and above with a primary diagnosis of AIS, were first identified using the ICD-10 code I63.x as previously reported in several studies. [10][11][12][13][14][15] I64.x codes are not available on HCUP's NIS 2019 repertoire. 8 Similarly, patients who reported a history of cannabis (use, abuse, or dependence) were also identified through CCSR code MBD019 and ICD-10-CM codes "F12.11" and "F12.21."…”
Section: Methodsmentioning
confidence: 99%
“…Patients of ages 25 and above with a primary diagnosis of AIS, were first identified using the ICD-10 code I63.x as previously reported in several studies 10–15 . I64.x codes are not available on HCUP’s NIS 2019 repertoire 8 .…”
Section: Methodsmentioning
confidence: 99%